RESOURCE MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE IN IMPROVING THE QUALITY OF EDUCATION IN PRIMARY SCHOOLS - Alaidin Alaidin; Nasir Usman; Bahrun Bahrun; Mariano Dos Santos (JETL (Journal of Education, Teaching and Learning), 2025)
Resource Management Of Educational Facilities And Infrastructure In Improving The Quality Of Education In Primary Schools. This research aims to determine the influence of educational facilities and infrastructure resources on improving the quality of education in elementary schools. This research uses descriptive quantitative methods. The participants involved consisted of 10 people including 5 principals and 5 deputy principals, each of whom came from 5 schools in the cluster of 35 SDN Lamreung, Aceh Besar Regency, namely SDN Lamreung, SDN Rumpet, SDN Lam Ujong, SDN Gla Meunasah Baro and SD Arrisilah Bilingual School. This research data collection technique uses observation, interviews and questionnaires. Research data analysis uses a qualitative approach obtained from observations and interviews, and a quantitative approach obtained from the results of filling out a questionnaire which is then processed using prerequisite tests and hypothesis testing using SPSS version 25.00. The results of this research show that the T test shows tcount 4.809 which is greater than ttable 2.306 At the level of significance, it can be concluded that there is an influence of facility and infrastructure resource management on increasing the quality of education in elementary schools.